Transforming dentistry : the rise and near demise of dentistry at Western University - Kenny, David J.; McKellar, Shelley (University of Toronto Press, 2022)
"The history of the dental program at Western University is a spirited and gritty story of grand visions, strong personalities, and contentious leadership. Focusing on the years from 1965 to 2015, Transforming Dentistry highlights Western University's ambitious plans to create and situate a dental program within a health sciences complex; the practical challenges involved in implementing a curriculum and populating a new school; the influence of key dental faculty, community dentists, and students in shaping the program; and the school's near closure during the 1990s. David J. Kenny and Shelley McKellar detail how and why the training of dentists was transformed by science, technology, and individual educators. The book focuses on the unique aspects of Western's dental program and situates it in comparison with Canada's other nine dental programs. Today, the strong reputation of Western's dental school is a direct result of the ambitious visions, professional commitment, and steadfast leadership employed by London dentists and university educators over more than five decades."--